Association of perceived male sexual dysfunction and sexually transmitted disease to female sexual function among Indonesian women (Medical Journal of Indonesia, 2023)
BACKGROUND Male sexual dysfunction (MSD)’s impact on female partners is challenging to understand. Male erectile dysfunction (ED) and ejaculation disorder likely affect female sexual function. This study aimed to examine the prevalence of female sexual dysfunction and disorder as well as the relationship between perceived MSD and female sexual function using the validated Indonesian short version of the 6-item Female Sexual Function Index (FSFI-6). METHODS This cross-sectional study was conducted at Cipto Mangunkusumo Hospital, Jakarta, Indonesia, from February 2018 to February 2019. About 702 Indonesian married women, including patients, visitors, and medical and nonmedical staff, provided the sociodemographic, FSFI-6, quality of life, and sexual function (ED, ejaculation disorder, and desire problems), and sexually transmitted disease (STD) data. The association between categorical variables was evaluated using Fisher’s test. Logistic regression was used for multivariate analysis, and a p-value of 0.05 was considered statistically significant. RESULTS Among 702 women, about 242 had sexual dysfunction (34.5%), 20 had sexual disorder (2.8%), 172 had low desire (24.5%), 72 had low arousal (10.3%), 253 had orgasmic function (36.0%), and 575 had sexual pain (81.9%). The respondents reported their partners’ STD, desire problems, ED, and ejaculation disorder. Female sexual disorder and low desire were associated with perceived ED. Female sexual disorder was associated with STD (Wald = 10.3, p = 0.001) and desire problems (Wald = 6.89, p = 0.008). No other MSD was associated with female sexual function. CONCLUSIONS Perceived STD and male desire problems affected female sexual disorder.